The level of accounting disclosure of social responsibility towards others from the auditors’ perspective at the Libyan Audit Bureau (Economic studies journal, 2025)
The study aimed to determine the levels of accounting disclosure towards others (society, customers, employees, and the environment) in companies and public institutions in Libya, from the auditors' perspective at the Libyan Audit Bureau. The descriptive analytical approach was used, due to its suitability for the purposes of the study, and to determine the level of disclosure, a five-point Likert scale was adopted (1= strongly disagree...5= strongly agree). A questionnaire was designed as a mean tool for collecting primary data, and was analyzed using one Sample-T test to determine the level of accounting disclosure. The population of the study was represented by auditors at the Audit Bureau who are assigned to audit the accounts of public entities. The number of distributed forms was (50) forms, distributed using a comprehensive inventory method due to the limited number of members assigned to the audit process, which amounted to (50) members. The study found that there is a somewhat acceptable level of accounting disclosure of social responsibility towards others in companies and public institutions. The study recommended increasing the degree of interest in disclosure and raising its levels towards others (society, customers, employees, and the environment). The study’s limitations were represented in its use of a single source for collecting data (the questionnaire), which means that the results may not be generalized, as they may be affected by the honesty and integrity of the participants.
Keywords: Accounting disclosure; social responsibility; Libyan Audit Bureau